Space weather effects on low latitude geomagnetic field and ionospheric plasma response - Veenadhari, B.; Alex, S. (My University, 2006)
Space weather disturbances caused by enhanced stream of solar plasma during solar flares and Coronal Mass ejections (CMEs) are known to disrupt communications, endanger satellite payloads and introduce severe errors in a variety of tracking and positioning systems. The phenomena known as geomagnetic storms are the most obvious features of space weather disturbances. Magnetic storms are fundamental disturbances in the magnetosphere and can significantly increase, or decrease ionopheric electron densities (termed positive or negative storms, respectively). Electric fields originating in the magnetosphere can penetrate to the equatorial and low-latitude ionosphere resulting in vertical motions that restructure the Fregion density profiles due to the height dependence of the recombination rate. The effect of space weather related perturbations in electric fields and currents in the equatorial and low latitude magnetic field associated with the changes in magnetospheric convection can be investigated using simultaneous observations from ground as well as ionospheric measurements. The present solar cycle witnessed many solar flares and coronal mass ejections (CMEs) which gave rise to intense geomagnetic storms due to highly active solar environment. The series of X-class solar flares occurred from 2 – 15 April 2001. The geomagnetic field was intermittently disturbed during period due to the CME passages. The geomagnetic storm began on 31 March and 11April 2001 are considered for the present study. These events were selected to study from ground based geomagnetic data, multi satellite data of solar wind and interplanetary parameters. Influence of the magnetospheric storm time electric field changes are estimated by the changes in the equatorial electric field as evidenced by the disturbance parameter of the equatorial electrojet strength and corresponding ionospheric response.
Keywords: Geomagnetic storms; Equatorial electrojet; Equatorial electric field; Ionosphere; Magnetosphere; Geomagnetic field; Coronal Mass ejection (CME)